On the basis of sex and sleep: the influence of the estrous cycle and sex on sleep-wake behavior - Swift, Kevin M.; Gary, Nicholas C.; Urbanczyk, Phillip J. (Frontiers in Neuroscience, 2024)
The recurrent hormonal fluctuations within reproductive cycles impact sleep-wake behavior in women and in rats and mice used in preclinical models of sleep research. Strides have been made in sleep-related clinical trials to include equal numbers of women; however, the inclusion of female rodents in neuroscience and sleep research is lacking. Female animals are commonly omitted from studies over concerns of the effect of estrus cycle hormones on measured outcomes. This review highlights the estrous cycle’s broad effects on sleep-wake behavior: from changes in sleep macroarchitecture to regionally specific alterations in neural oscillations. These changes are largely driven by cycle-dependent ovarian hormonal fluctuations occurring during proestrus and estrus that modulate neural circuits regulating sleep-wake behavior. Removal of estrous cycle influence by ovariectomy ablates characteristic sleep changes. Further, sex differences in sleep are present between gonadally intact females and males. Removal of reproductive hormones via gonadectomy in both sexes mitigates some, but not all sex differences. We examine the extent to which reproductive hormones and sex chromosomes contribute to sex differences in sleep-wake behavior. Finally, this review addresses the limitations in our understanding of the estrous cycle’s impact on sleep-wake behavior, gaps in female sleep research that are well studied in males, and the implications that ignoring the estrous cycle has on studies of sleep-related processes.